Therapeutic potential of CERE-110 (AAV2-NGF): Targeted, stable, and sustained NGF delivery and trophic activity on rodent basal forebrain cholinergic neurons - Bishop, Kathie M.; Hofer, Eva K.; Mehta, Arpesh; Ramirez, Anthony; Sun, Liangwu; Tuszynski, Mark; Bartus, Raymond T. (Experimental neurology, 2008)
Treatment of degenerating basal forebrain cholinergic neurons with nerve growth factor (NGF) in Alzheimer's disease has long been contemplated, but an effective and safe delivery method has been lacking. Towards achieving this goal, we are currently developing CERE-110, an adeno-associated virus-based gene delivery vector that encodes for human NGF, for stereotactic surgical delivery to the human nucleus basalis of Meynert. Results indicate that NGF transgene delivery to the targeted brain region via CERE-110 is reliable and accurate, that NGF transgene distribution can be controlled by altering CERE-110 dose, and that it is possible to achieve restricted NGF expression limited to but covering the target brain region. Results from animals examined at longer time periods of 3, 6, 9 and 12 months after CERE-110 delivery indicate that NGF transgene expression is stable and sustained at all time points, with no loss or build-up of protein over the long-term. In addition, results from a series of experiments indicate that CERE-110 is neuroprotective and neurorestorative to basal forebrain cholinergic neurons in the rat fimbria–fornix lesion and aged rat models, and has bioactive effects on young rat basal forebrain cholinergic neurons. These findings, as well as those from several additional non-clinical experiments conducted in both rats and monkeys, led to the initiation of a Phase I clinical study to evaluate the safety and efficacy of CERE-110 in Alzheimer's disease subjects, which is currently ongoing.